Analisis Pengaruh PDRB Per Kapita, Jumlah Penduduk Miskin dan Investasi Terhadap Indeks Pembangunan Manusia (IPM) di Provinsi Kalimantan Timur Tahun 2017-2021 - Williyan, Ergi Armanda; Hasmarini, Maulidyah Indiria (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2024)
Development is influenced by several factors, one of which is the quality of human resources which is usually represented by the Human Development Index (IPM) which is an indicator of achieving higher quality human development. This study aims to analyze the effect of Per Capita GRDP, Number of Poor Population and Investment on the Human Development Index in 10 Regencies/Cities in East Kalimantan Province in 2017-2021. This research uses panel data analysis method with the selected model Fixed effect Model (FEM) and uses eviews 10 software. From the results of this study it can be concluded that partially the variables PDRB Per Capita, Domestic Investment (PMDN) and Poverty have a positive effect on IPM while for the variable Foreign Investment (PMA) has no effect on IPM.